PENGARUH IMPLEMENTASI KINERJA LINGKUNGAN TERHADAP RETURN SAHAM YANG DIMODERASI CORPORATE GOVERNANCE - Eny Purwaningsih (Fakultas Ekonomi, Universitas Negeri Jakarta, 2017)
The purpose of this research is to determinethe influence ofimplementation environmentalperformance onstock returnwith corporate governance as moderating variable. Cumulative Abnormal Return used as a proxy for stock return. Dataforthis research were obtainedfrom secondary data by purposive sampling method. There are 85 manufacturing companieslisted in IDX complying with PROPER KLH RI on 2013-2017that used as sample. This research usessimple linear regression technique as method of analysis. This research results show that the implementationenvironmental performance has a positive influence to stock return. The results on moderating variable show that the corporate governance use proxy is skill of independent commissioner and skill of audit committee did not mediaterelation between the environmental performance withstock return. Keywords: Stock return, environmental performance, PROPER, corporate governance, independent commissioner, and audit committee.